Typical pantothenate kinase-associated neurodegeneration caused by compound heterozygous mutations in PANK2 gene in a Chinese patient: a case report and literature review - Tao, Yilun; Zhao, Chen; Han, Dong; Wei, Yiju; Wang, Lihong; Song, Wenxia; Li, Xiaoze (Frontiers in Neurology, 2023)
Pantothenate kinase-associated neurodegeneration (PKAN) is a rare genetic neurodegenerative disorder with brain iron accumulation characterized as dysarthria, spasticity, cognitive impairment, parkinsonism, and retinopathy. PKAN is caused by biallelic mutations in the mitochondrial pantothenate kinase 2 (PANK2) gene. Herein, we report a 4-year-old patient with PKAN from a Han Chinese family, who presented with developmental regression, progressive inability to walk, and limb tremors. Neuroimaging demonstrated “eye-of-the-tiger” sign. Whole exome sequencing (WES) identified compound heterozygous mutations of c.1213T>G (p.Tyr405Asp) and c.1502T>A (p.Ile501Asn) in PANK2 gene. In addition, a review of all known PANK2 variants observed in reported PKAN patients was conducted, to improve understanding of the genotype-phenotype associations that occur in PKAN patients.